Carbon fiber reinforced modified resin material and preparation method thereof
By acidizing carbon fibers, silane coupling agents to modify graphene oxide and introducing polyethylene glycol and alkylphenol polyoxyethylene ether, the problems of poor fracture toughness and insufficient bonding of carbon fiber reinforced modified resin materials are solved, and its mechanics are significantly improved Performance has expanded applications in the field of high-performance composite materials.
Patent Information
- Application Number
- CN202411644042.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The carbon fiber-reinforced modified resin composite materials have poor fracture toughness in high impact and high load environments, high processing costs of thermosetting resins, and insufficient binding properties with carbon fiber, which limits their application in aerospace and military fields.
By acidizing the modified carbon fibers, silane coupling agents to modify graphene oxide, and polyethylene glycol and alkylphenol polyoxyethylene ether are introduced to enhance the interface bonding between the carbon fiber and the resin matrix and improve the mechanical properties of the material.
It significantly improves the mechanical properties of carbon fiber reinforced modified resin composite materials and enhances its application prospects in aerospace, automobile manufacturing and other fields.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer compound compositions, and in particular relates to a carbon fiber reinforced modified resin material and a preparation method thereof. Background Art
[0002] Carbon fiber reinforced modified resin refers to a composite material with resin as the matrix material and carbon fiber as the reinforcement material. With the advancement of science and technology and the acceleration of industrialization, especially in the fields of automobile lightweighting, aerospace technology innovation and military equipment upgrading, the requirements for material strength, stiffness, heat resistance and lightweight are becoming increasingly stringent. Carbon fiber resin-based composite materials are widely used in main load-bearing structural parts and precision support components in the automotive, aerospace and military fields due to their excellent properties such as high specific strength, specific modulus and small thermal expansion coefficient.
[0003] However, despite the many advantages of carbon fiber reinforced modified resin composites, they still face a series of technical defects in current research and applications, which hinder their wider application and performance optimization.
[0004] First, as a commonly used matrix material, thermosetting resins have good heat resistance and dimensional stability due to their highly cross-linked network structure, but this structure also brings inherent brittleness, resulting in poor fracture toughness of the material. This characteristic limits the application of composite materials in extreme environments such as high impact and high load, especially in the aerospace and military fields that need to withstand complex stress states.
[0005] In addition, the thermosetting resin matrix requires a higher temperature during the curing process, which not only increases processing costs and energy consumption, but may also cause thermal damage to the carbon fiber. At the same time, the compatibility of thermosetting resins with other matrix materials is poor, which limits the application of composite materials in multi-material systems. In addition, the high viscosity of the resin at room temperature during processing leads to poor fluidity, making it difficult to fully infiltrate the gaps between carbon fiber bundles, affecting the density and uniformity of the composite material, thereby reducing its mechanical properties.
[0006] Finally, the performance of the interface layer between carbon fiber and resin matrix is a key factor affecting the overall performance of the composite material. Due to the inertness of the carbon fiber surface and the lack of polar functional groups, the bonding force between the unmodified carbon fiber and the resin matrix is weak and the interface layer is fragile. This not only reduces the mechanical properties and durability of the composite material, but may also cause debonding or delamination at the interface during the stress process, further weakening the overall performance of the material.
[0007] In summary, although carbon fiber reinforced modified resin composites have great potential in improving material properties and expanding application areas, the brittleness and poor compatibility of the matrix resin, the fragility of the interface layer, and the poor bonding between the resin and the carbon fiber still limit the practical application of carbon fiber reinforced modified resin composites in various high-precision fields. Summary of the invention
[0008] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0009] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0010] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a carbon fiber reinforced modified resin material.
[0011] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising: 40-60 parts of acidified carbon fiber, 8-12 parts of graphene oxide modified by silane coupling agent, 10-20 parts of polyethylene glycol, and 3-8 parts of alkylphenol polyoxyethylene ether are uniformly mixed by ultrasonication with acetone as solvent to obtain a mixture I; 100 parts of epoxy resin and 30-50 parts of curing agent are mixed, and heated and stirred until melted to obtain mixture II; The mixture I and the mixture II are placed in a vacuum oven for mixing and stirring, and the obtained product is placed at room temperature and then heated for curing to obtain a carbon fiber reinforced modified resin material.
[0012] As a preferred embodiment of the method for preparing the carbon fiber reinforced modified resin material of the present invention, the method for preparing the acidified carbon fiber is: The carbon fiber and acetone were ultrasonically mixed in a mass volume ratio of 1 g: 10-15 ml, and then placed in a three-necked flask, refluxed at 60-70°C for 24-48 hours, and after the reflux was completed, the supernatant was removed by centrifugation, and then vacuum dried; The obtained product is reacted with a mixed strong acid at a mass volume ratio of 1g:10~15ml at 70~80℃ for 2~3h. After the reaction, the supernatant is removed by centrifugation, deionized water and anhydrous ethanol are added for shaking, and the washing is repeated until the pH of the solution is alkaline, and then vacuum drying is performed to obtain acidified carbon fiber.
[0013] As a preferred embodiment of the method for preparing the carbon fiber reinforced modified resin material of the present invention, the mixed strong acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1-3:1-3.
[0014] As a preferred embodiment of the method for preparing the carbon fiber reinforced modified resin material of the present invention, the method for preparing the graphene oxide modified by the silane coupling agent is as follows: γ-aminopropyltriethoxysilane and water are mixed in a volume ratio of 1-3:9, and ultrasonicated for 30-60 minutes to obtain a silane coupling agent hydrolyzate; Graphene oxide powder and dispersant were added thereto, and ultrasonic treatment was continued for 30 minutes. After uniform dispersion, the temperature was raised to 80-90° C. and the reaction was carried out for 6-8 hours. The product was filtered and dried to obtain graphene oxide modified with a silane coupling agent.
[0015] As a preferred embodiment of the method for preparing the carbon fiber reinforced modified resin material of the present invention, the mass fraction of the graphene oxide in the silane coupling agent hydrolyzate is 15-25%, and the mass ratio of the graphene oxide to the dispersant is 1:0.1-0.3.
[0016] As a preferred embodiment of the method for preparing the carbon fiber reinforced modified resin material of the present invention, the heating and stirring to melt to obtain the mixture II is performed at a temperature of 55 to 75° C. and a time of 10 to 20 min.
[0017] As a preferred embodiment of the method for preparing the carbon fiber reinforced modified resin material of the present invention, the mixture I and the mixture II are placed in a vacuum oven for mixing and stirring, wherein the mixing and stirring temperature is 55-60°C and the time is 2-4 hours.
[0018] As a preferred embodiment of the method for preparing the carbon fiber reinforced modified resin material of the present invention, the obtained product is placed at room temperature and then subjected to temperature-raising curing treatment, wherein the time of placing at room temperature is 10 to 14 hours.
[0019] As a preferred embodiment of the method for preparing the carbon fiber reinforced modified resin material of the present invention, the curing treatment is carried out at a temperature of 70-90° C. and for a time of 2-4 hours.
[0020] Beneficial effects of the present invention: The present invention improves the surface properties of the carbon fibers by acidifying the carbon fibers, increases the number of functional groups on the surface, and thus improves the interface bonding force between the carbon fibers and the resin matrix. By modifying graphene oxide with a silane coupling agent, the compatibility between graphene oxide and the resin matrix is improved, and the interface bonding force is enhanced; The introduction of high molecular weight polymer polyethylene glycol as a bridge molecule can connect the modified GO and the epoxy resin matrix. The hydroxyl groups of PEG form chemical bonds with the silane functional groups on the surface of the modified GO and the epoxy functional groups in the epoxy resin, thereby enhancing the interfacial bonding between GO and the resin matrix. The introduction of non-ionic surfactant alkylphenol polyoxyethylene ether has both dispersing effect and certain adhesive properties. It can act as a plasticizer in the resin to increase the fluidity of the resin. It also helps to improve the dispersibility of other fillers (such as carbon fiber, graphene oxide, etc.) in the resin. The present invention significantly improves the interfacial bonding strength of carbon fiber reinforced modified resin composites by in-depth analysis of the interaction mechanism between the components and rationally designs the formula, thereby improving the overall mechanical properties of the composites. It has broad application prospects in fields requiring high-performance composite materials such as aerospace, automobile manufacturing, and electronic appliances. DETAILED DESCRIPTION
[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0022] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0023] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0024] The carbon fiber used in the present invention is T700 carbon fiber, the epoxy resin used is bisphenol A epoxy resin, the polyethylene glycol used is polyethylene glycol 6000, and the alkylphenol polyoxyethylene ether used is alkylphenol polyoxyethylene ether TX-10, all of which are purchased from Jiangsu Santuo New Materials Co., Ltd., and the remaining raw materials are all commonly available in the market unless otherwise specified.
[0025] In the performance test of the present invention, the tensile strength is measured with reference to the standard (GB / T3354-1999; the impact toughness is measured with reference to the standard GBT1451-2005.
[0026] Example 1: This example provides a method for preparing a carbon fiber reinforced modified resin material, specifically: 1) 1g carbon fiber was ultrasonically mixed with 10mL acetone and then placed in a three-necked flask, refluxed at 70°C for 48h, centrifuged for 0.5h after the reflux, and vacuum dried after removing the supernatant. The obtained product was acidified with 10mL of a mixed strong acid solution prepared by concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1 at 80°C for 3h. After the reaction, the supernatant was removed by centrifugation, deionized water and anhydrous ethanol were added for shaking, and the washing was repeated until the solution pH = 7, and then vacuum dried to obtain acidified carbon fiber; γ-aminopropyltriethoxysilane and water were mixed in a volume ratio of 1:9 and ultrasonically treated for 30 minutes to obtain a silane coupling agent hydrolyzate, graphene oxide powder and calcium lignin sulfonate (dispersant) were added thereto and ultrasonically treated for 30 minutes, wherein the mass fraction of graphene oxide in the silane coupling agent hydrolyzate was 20%, and the mass ratio of graphene oxide to calcium lignin sulfonate was 1:0.1. After being evenly dispersed, the temperature was raised to 90° C. and reacted for 6 hours. The product was filtered and dried to obtain graphene oxide modified by a silane coupling agent; 50 parts of acidified carbon fiber, 10 parts of graphene oxide modified by a silane coupling agent, 15 parts of polyethylene glycol, and 5 parts of alkylphenol polyoxyethylene ether are uniformly mixed by ultrasonication with acetone as a solvent to obtain a mixture I; 100 parts of epoxy resin and 40 parts of triethylenediamine were mixed, heated and stirred at 60° C. for 10 minutes to obtain a mixture II; The mixture I and the mixture II were placed in a 55° C. vacuum oven and mixed and stirred for 3 h. The obtained product was placed at room temperature for 10 h and then heated to 80° C. for curing for 3 h, thereby obtaining the carbon fiber reinforced modified resin material of this embodiment.
[0027] Comparative Example 1: This comparative example is different from Example 1 in that step 1 is omitted and the carbon fiber is not subjected to acidification treatment. Specifically: 50 parts of carbon fiber, 10 parts of graphene oxide modified by a silane coupling agent, 15 parts of polyethylene glycol, and 5 parts of alkylphenol polyoxyethylene ether are uniformly mixed by ultrasonication with acetone as a solvent to obtain a mixture I; 100 parts of epoxy resin and 40 parts of triethylenediamine were mixed, heated and stirred at 60° C. for 10 minutes to obtain a mixture II; Mixture I and mixture II were placed in a vacuum oven at 55°C and stirred for 3 hours. The resulting product was placed at room temperature for 10 hours and then heated to 80°C for curing for 3 hours. The remaining steps and processes are all referred to Example 1 to obtain the carbon fiber reinforced modified resin material of this comparative example.
[0028] Comparative Example 2: This comparative example is different from Example 1 in that step 2 is omitted) and the graphene oxide is not subjected to silane coupling agent modification treatment. Specifically: 50 parts of acidified carbon fiber, 10 parts of graphene oxide, 15 parts of polyethylene glycol, and 5 parts of alkylphenol polyoxyethylene ether are uniformly mixed by ultrasonication with acetone as solvent to obtain a mixture I; 100 parts of epoxy resin and 40 parts of triethylenediamine were mixed, heated and stirred at 60° C. for 10 minutes to obtain a mixture II; Mixture I and mixture II were placed in a vacuum oven at 55°C and stirred for 3 hours. The resulting product was placed at room temperature for 10 hours and then heated to 80°C for curing for 3 hours. The remaining steps and processes are all referred to Example 1 to obtain the carbon fiber reinforced modified resin material of this comparative example.
[0029] Comparative Example 3: This comparative example is different from Example 1 in that the polyethylene glycol in step 3) is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the carbon fiber reinforced modified resin material of this comparative example.
[0030] Comparative Example 4: This comparative example is different from Example 1 in that the alkylphenol polyoxyethylene ether in step 3) is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the carbon fiber reinforced modified resin material of this comparative example.
[0031] The properties of the carbon fiber reinforced modified resin materials prepared in Comparative Example 1 and Comparative Examples 1 to 4 are shown in Table 1.
[0032] Table 1 Tensile strength (MPa) <![CDATA[Impact toughness (KJ / m 2 )]]> Interlaminar shear strength (MPa) Example 1 1816 218 129 Comparative Example 1 1399 122 62 Comparative Example 2 1022 117 57 Comparative Example 3 985 94 48 Comparative Example 4 1577 161 77 It can be seen from Table 1 that the steps of acid treatment of carbon fiber, modification of graphene oxide with silane coupling agent, addition of polyethylene glycol and alkylphenol polyoxyethylene ether play an important role in improving the mechanical properties of carbon fiber reinforced modified resin materials. The absence or omission of these steps will lead to a significant decrease in the tensile strength, impact toughness and interlaminar shear strength of the composite material.
[0033] This is because the acid treatment can improve the surface properties of carbon fiber and increase the number of functional groups on its surface, thereby improving the interfacial bonding strength between the carbon fiber and the resin matrix. The carbon fiber that has not been acid treated has fewer surface functional groups and weaker bonding strength with the resin matrix, resulting in a decrease in the tensile strength, impact toughness and interlaminar shear strength of the composite material.
[0034] Silane coupling agent can improve the compatibility between graphene oxide and resin matrix and enhance the interfacial bonding force. Graphene oxide that has not been modified with silane coupling agent has poor dispersibility in the resin matrix and is easy to form agglomerates, resulting in a decrease in the mechanical properties of the composite material. At the same time, the interfacial bonding force between unmodified graphene oxide and the resin matrix is weak, further reducing the tensile strength, impact toughness and interlaminar shear strength of the composite material.
[0035] In the present invention, polyethylene glycol, as a high molecular polymer, has both a dispersing effect and a certain adhesive property. After omitting polyethylene glycol, the dispersibility and adhesive properties of the composite material will be affected. The dispersion of graphene oxide in the resin matrix is uneven, and the interface bonding force between the carbon fiber and the resin matrix is weakened. These factors together lead to a decrease in the tensile strength, impact toughness and interlaminar shear strength of the composite material.
[0036] Alkylphenol polyoxyethylene ether is a non-ionic surfactant with good dispersibility and certain adhesion properties. After omitting alkylphenol polyoxyethylene ether, the dispersibility of the composite material is reduced, the dispersion of graphene oxide in the resin matrix is uneven, and agglomerates are easily formed. At the same time, the adhesion performance of alkylphenol polyoxyethylene ether is also affected, resulting in a weakened interface bonding force between carbon fiber and resin matrix. These factors will also lead to a decrease in the tensile strength, impact toughness and interlaminar shear strength of the composite material.
[0037] Example 2: This example is used to explore the effects of different carbon fiber treatment methods on the properties of the obtained carbon fiber reinforced modified resin material. Specifically, the acidification treatment of the carbon fiber in step 1) of Example 1 is adjusted to be: A. dopaminization; Use 10 mmol / l Tris buffer solution to prepare a 2 mg / mL dopamine solution; The carbon fiber was refluxed with acetone at 100 °C for 24 h, and the obtained product was placed in a dopamine solution and soaked at room temperature for 24 h, then taken out and washed with deionized water for several times until the filtrate was colorless and transparent. Finally, the fiber was placed in a vacuum oven at 60 °C and dried overnight to obtain dopamine carbon fiber.
[0038] Silanization; At 60°C, the carbon fiber was added to an ethanol solution with a KH570 concentration of 3 wt%, and reacted for 8 h under magnetic stirring to obtain silanized carbon fiber.
[0039] Air oxidation; The carbon fiber is subjected to air oxidation treatment at 500° C. for 1.5 h to obtain air-oxidized carbon fiber.
[0040] The rest of the preparation methods are all based on Example 1, except that the acidified carbon fiber is replaced with other functionalized carbon fibers to obtain the carbon fiber reinforced modified resin material made from different functionalized carbon fibers of this example, and the relevant properties thereof are measured and compared with those of Example 1. The results are shown in Table 2.
[0041] Table 2 Processing Tensile strength (MPa) <![CDATA[Impact toughness (KJ / m 2 )]]> Interlaminar shear strength (MPa) acidification 1816 218 129 Dopaminization 1422 123 99 Silanization 1652 187 89 Air oxidation 1190 116 65 It can be seen from Table 2 that in the scheme of the present invention, different functional treatment methods of carbon fiber have a significant effect on the performance of the obtained carbon fiber reinforced modified resin material. For example, dopamine treatment may form a thicker coating on the surface of the carbon fiber. Although this coating may improve the wettability and adhesion between the carbon fiber and the resin matrix, it may also introduce additional stress concentration points, resulting in a decrease in the mechanical properties of the composite material. In addition, if the dopamine coating fails to evenly cover the surface of the carbon fiber, local defects may be formed, further weakening the mechanical properties of the composite material.
[0042] The mechanical properties of composite materials prepared from carbon fibers after silanization treatment decrease to a certain extent. At this time, the silane coupling agent fails to effectively penetrate into the pores of the carbon fibers or fails to form a good chemical bond with the resin matrix, resulting in a weakening of the interfacial bonding force, thereby reducing the mechanical properties of the composite materials.
[0043] Air oxidation treatment is a relatively mild method for carbon fiber surface modification. It cannot effectively remove impurities on the carbon fiber surface and increase the number of functional groups like acid treatment. In addition, air oxidation treatment may also introduce some oxidation products or defects that are not conducive to mechanical properties.
[0044] Example 3. The difference between this example and Example 1 is that the amount of acidified carbon fiber in step 3) is adjusted to 30 parts, 40 parts, 50 parts, 60 parts, and 70 parts, respectively, and the remaining steps and processes are all referred to Example 1, in order to explore the effect of the amount of acidified carbon fiber on the performance of the modified resin material obtained, and the relevant properties of the modified resin materials obtained with different acidified carbon fiber contents are tested, and the results are shown in Table 3.
[0045] Table 3 Carbon fiber content Tensile strength (MPa) <![CDATA[Impact toughness (KJ / m 2 )]]> Interlaminar shear strength (MPa) 30 servings 982 98 45 40 servings 1578 163 86 50 servings 1816 218 129 60 servings 1762 154 98 70 servings 1421 112 74 As can be seen from Table 3, the content of acidified carbon fiber has a significant effect on the performance of the modified resin material. Too high or too low content of acidified carbon fiber may lead to an increase in the unevenness of the interface bonding force, and in the composite material, the resin matrix plays a role in supporting and transferring the load. When the content of acidified carbon fiber changes, the relative ratio of the resin matrix will also change. If the content of acidified carbon fiber is too high, the proportion of the resin matrix will be relatively reduced, which will lead to a decrease in the toughness of the composite material; on the contrary, if the content is too low, the proportion of the resin matrix may be too high, affecting the rigidity and strength of the composite material.
[0046] Example 4. This example is different from Example 1 in that the amount of silane coupling agent-modified graphene oxide in step 3) is adjusted to 6 parts, 8 parts, 10 parts, 12 parts, and 14 parts, respectively. The remaining steps and processes are all referred to Example 1, in order to explore the effect of the amount of silane coupling agent-modified graphene oxide on the properties of the modified resin material obtained, and the relevant properties of the modified resin material obtained with different amounts of silane coupling agent-modified graphene oxide are tested, and the results are shown in Table 4.
[0047] Table 4 Graphene oxide content Tensile strength (MPa) <![CDATA[Impact toughness (KJ / m 2 )]]> Interlaminar shear strength (MPa) 6 servings 1033 112 59 8 servings 1482 151 93 10 servings 1816 218 129 12 servings 1573 149 108 14 servings 1268 125 87 It can be seen from Table 4 that the amount of graphene oxide modified by silane coupling agent has a significant effect on the performance of the modified resin material. The modification of silane coupling agent can enhance the interface interaction between GO and the resin matrix. However, when the content of modified GO is too high or too low, the uniformity of the interface interaction may be affected. If the content of modified GO is too high, the resin matrix may not be able to fully infiltrate the GO sheet, forming interface defects; while if the content is too low, the interface bonding force between GO and the resin matrix may be insufficient.
[0048] Example 5. This example is different from Example 1 in that the amount of polyethylene glycol in step 3) is adjusted to 5 parts, 10 parts, 15 parts, 20 parts, and 25 parts, respectively. The remaining steps and processes are all based on Example 1, in order to explore the effect of the amount of polyethylene glycol on the properties of the modified resin material. The relevant properties of the modified resin materials obtained with different amounts of polyethylene glycol are tested, and the results are shown in Table 5.
[0049] Table 5 Polyethylene glycol content Tensile strength (MPa) <![CDATA[Impact toughness (KJ / m 2 )]]> Interlaminar shear strength (MPa) 5 servings 873 92 57 10 servings 1323 135 102 15 servings 1816 218 129 20 servings 1622 184 110 25 servings 1180 145 107 In the scheme of the present invention, the addition of polyethylene glycol can optimize the internal structure of the composite material, so that a tighter combination is formed between the epoxy resin, the carbon fiber and the modified GO. This tight combination helps to improve the overall mechanical properties of the composite material. Specifically, polyethylene glycol, as a high molecular polymer, has a strong hydrophilicity and can form hydrogen bonds with the resin group, thereby playing a plasticizing role. Its addition may also change the structure of the resin matrix, including its cross-linking density, molecular chain length, etc. When the PEG content is too high, it may interfere with the normal cross-linking process of the resin matrix, resulting in a decrease in the cross-linking density, thereby affecting the mechanical properties of the composite material.
[0050] The acidified carbon fiber surface contains acidic functional groups such as carboxyl, which can form hydrogen bonds with the hydroxyl groups in PEG. The formation of hydrogen bonds enhances the interaction between PEG and carbon fiber, which helps to improve the dispersibility and interfacial bonding of carbon fiber in the epoxy resin matrix. At the same time, the good hydrophilicity of PEG can wet the carbon fiber surface, reduce the interfacial tension between carbon fiber and epoxy resin matrix, and promote the infiltration and coating of the resin matrix on the carbon fiber, thereby improving their bonding effect.
[0051] In summary, PEG can be used as a bridge molecule to connect modified GO and epoxy resin matrix. The hydroxyl groups of PEG form chemical bonds or hydrogen bonds with the silane functional groups on the surface of modified GO and the epoxy functional groups in the epoxy resin, thereby enhancing the interfacial bonding between GO and the resin matrix.
[0052] However, when the content of polyethylene glycol is too high, its plasticizing effect may weaken the molecular chain interaction of the resin matrix, thereby affecting the mechanical properties of the composite material. An appropriate amount of PEG can form a good interaction with the resin matrix to improve the interfacial bonding and dispersibility of the composite material. However, when the PEG content is too high or too low, this interaction may become uneven, resulting in defects or stress concentration points inside the composite material.
[0053] Example 6. This example is different from Example 1 in that the amount of alkylphenol polyoxyethylene ether in step 3) is adjusted to 1 part, 3 parts, 5 parts, 8 parts, and 10 parts, respectively. The remaining steps and processes are all based on Example 1, in order to explore the effect of the amount of alkylphenol polyoxyethylene ether on the properties of the modified resin material obtained, and the relevant properties of the modified resin material obtained with different amounts of alkylphenol polyoxyethylene ether are tested. The results are shown in Table 6.
[0054] Table 6 Alkylphenol polyoxyethylene ether content Tensile strength (MPa) <![CDATA[Impact toughness (KJ / m 2 )]]> Interlaminar shear strength (MPa) 1 serving 988 101 65 3 servings 1445 154 98 5 servings 1816 218 129 8 servings 1568 175 102 10 servings 1238 139 87 Since the molecular structure of alkylphenol polyoxyethylene ether contains benzene rings and polyoxyethylene ether groups, these functional groups can interact with the functional groups in the resin matrix. An appropriate amount of alkylphenol polyoxyethylene ether can form a good interaction with the resin matrix and improve the interfacial bonding force and dispersibility of the composite material. However, when the content of alkylphenol polyoxyethylene ether is too high, it may interfere with the normal cross-linking process of the resin matrix, resulting in a decrease in the cross-linking density, thereby affecting the mechanical properties of the composite material.
[0055] In addition, as a nonionic surfactant, alkylphenol polyoxyethylene ether can act as a plasticizer in the resin, increase the fluidity of the resin, and also help improve the dispersion of other fillers (such as carbon fiber, graphene oxide, etc.) in the resin. However, when the content of alkylphenol polyoxyethylene ether is too high or too low, its plasticization and dispersion may become uneven, resulting in defects or stress concentration points inside the resin.
[0056] In summary, the present invention is based on the defects of the existing carbon fiber reinforced modified resin composite materials, such as the brittleness and poor compatibility of the matrix resin, the fragility of the interface layer, and the poor bonding between the resin and the carbon fiber. The epoxy resin is used as the matrix, the carbon fiber is acidified, and combined with graphene oxide modified by a silane coupling agent, polyethylene glycol, and alkylphenol polyoxyethylene ether. By deeply analyzing the interaction mechanism between the components and rationally designing the formula, the interfacial bonding force of the carbon fiber reinforced modified resin composite material is significantly improved, thereby improving the overall mechanical properties of the composite material. The present invention has broad application prospects in the fields of high-performance composite materials such as aerospace, automobile manufacturing, and electronic appliances.
[0057] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a carbon fiber reinforced modified resin material, characterized in that: include, 40-60 parts of acidified carbon fiber, 8-12 parts of graphene oxide modified by silane coupling agent, 10-20 parts of polyethylene glycol, and 3-8 parts of alkylphenol polyoxyethylene ether are uniformly mixed by ultrasonication with acetone as solvent to obtain a mixture I; 100 parts of epoxy resin and 30-50 parts of curing agent are mixed, and heated and stirred until melted to obtain mixture II; The mixture I and the mixture II are placed in a vacuum oven for mixing and stirring, and the obtained product is placed at room temperature and then heated for curing to obtain a carbon fiber reinforced modified resin material.
2. The method for preparing a carbon fiber reinforced modified resin material according to claim 1, characterized in that: The preparation method of the acidified carbon fiber is: The carbon fiber and acetone were ultrasonically mixed in a mass volume ratio of 1 g: 10-15 ml, and then placed in a three-necked flask, refluxed at 60-70°C for 24-48 hours, and after the reflux was completed, the supernatant was removed by centrifugation, and then vacuum dried; The obtained product is reacted with a mixed strong acid at a mass volume ratio of 1g:10~15ml at 70~80℃ for 2~3h. After the reaction, the supernatant is removed by centrifugation, deionized water and anhydrous ethanol are added for shaking, and the washing is repeated until the pH of the solution is alkaline, and then vacuum drying is performed to obtain acidified carbon fiber.
3. The method for preparing a carbon fiber reinforced modified resin material according to claim 2, characterized in that: The mixed strong acid is obtained by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1-3:1-3.
4. The method for preparing a carbon fiber reinforced modified resin material according to claim 1, characterized in that: The preparation method of the silane coupling agent-modified graphene oxide is: γ-aminopropyltriethoxysilane and water are mixed in a volume ratio of 1-3:9, and ultrasonicated for 30-60 minutes to obtain a silane coupling agent hydrolyzate; Graphene oxide powder and dispersant were added thereto, and ultrasonic treatment was continued for 30 minutes. After uniform dispersion, the temperature was raised to 80-90° C. and the reaction was carried out for 6-8 hours. The product was filtered and dried to obtain graphene oxide modified with a silane coupling agent.
5. The method for preparing a carbon fiber reinforced modified resin material according to claim 4, characterized in that: The mass fraction of the graphene oxide in the silane coupling agent hydrolyzate is 15-25%, and the mass ratio of the graphene oxide to the dispersant is 1:0.1-0.
3.
6. The method for preparing a carbon fiber reinforced modified resin material according to claim 1, characterized in that: The heating and stirring are performed until the mixture is melted to obtain a mixture II, wherein the heating and stirring temperature is 55-75° C. and the heating and stirring time is 10-20 min.
7. The method for preparing a carbon fiber reinforced modified resin material according to claim 1, characterized in that: The mixture I and the mixture II are placed in a vacuum oven for mixing and stirring, wherein the mixing and stirring temperature is 55-60° C. and the time is 2-4 hours.
8. The method for preparing a carbon fiber reinforced modified resin material according to claim 1, characterized in that: The obtained product is placed at room temperature and then subjected to temperature-raising curing treatment, wherein the time of placing at room temperature is 10 to 14 hours.
9. The method for preparing a carbon fiber reinforced modified resin material according to claim 8, characterized in that: The curing treatment is performed at a temperature of 70 to 90° C. and for a time of 2 to 4 hours.
10. The carbon fiber reinforced modified resin material prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of composite carbon fiber / graphene oxide / organosilicone resin multidimensional hybrid material
CN104151581A
Preparation method of carbon fiber / graphene / epoxy resin prepreg and carbon fiber composite material
CN105968718A
Carbon fiber reinforced resin based high-performance light composite material and preparation method thereof
CN107936273A
KR20230001090A
Cited By
Carbon fiber reinforced modified resin material and preparation method thereof
CN120173366A
Carbon fiber directionally-distributed high-thermal-conductivity sealing paste and preparation method thereof
CN120518981A
Carbon fiber oriented distribution high thermal conductivity sealed paste and preparation method thereof
CN120518981B
